Las finanzas de las ciudades novohispanas ante el reformismo borbónico - Yovana Celaya Nández (Mélanges de la Casa de Velázquez, 2016)
The reform processes in the Spanish Monarchy can and need to be considered in terms of institutional political, economic and fiscal effects, and of its manifold jurisdictions: councils, provinces and kingdoms. This paper analyses the fiscal and institutional effects of a project for the reform of local finances in New Spain. The analysis focuses on the dialogue between the agents of reform and their interlocutors and how reform offered local authorities the means of reinforcing their tax collection powers, for instance through arbitrios.